The Challenges of Character Education: Mental Revolution Policy in the Development of Citizenship Education in Higher Education - Trisiana, Anita; Sugiaryo,; Rispantyo, (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to answer the challenges of character education in Indonesia. As a part of evaluating mental revolution policies, the priorities in the development of citizenship education is Nationalism-based character education. Character Education is an alternative model that synergizes with government programs through the revolutionary movement. The method used in this research was Research and Development (RnD). Data collection techniques used were interviews, observation in private and public universities in Central Java, Indonesia. It consisted of 118 universities. CIPP (Context, Input, Process, Product) used as an indicator of success in supporting the development of character education in citizenship education learning. In the Context component, the content of policies were analyzed based on educational policy patterns as part of citizen competencies. In the Input Aspect, it was analyzed based on the evaluation of learning provided to solve the problems in teaching and learning process. While in the Process aspect, it was analyzed based on the anticipation of citizenship issues. Furthermore, in the Product aspect, it was based on the importance of a stronger and more organized partnerships between government officials in the education sector and local governments. As such, it refers to the behavior that reflect to the superior personalities as educational resources.